Cost minimization analysis of a hexavalent vaccine in Argentina - Ignacio Olivera; Carlos Grau Pérez; Luis Lazarov; Eduardo Lopez; Cristian Oddo; Hugo Dibarboure (BMC, 2023)
Abstract Background Argentina currently uses a pentavalent vaccine containing diphtheria, tetanus, pertussis (whole cell), Haemophilus influenza type b and hepatitis B antigens, administered concomitantly with the inactivated polio vaccine (IPV) (DTwP-Hib-HB plus IPV) in its childhood vaccination schedule. However, hexavalent vaccines containing acellular pertussis antigens (DTaP-Hib-HB-IPV) and providing protection against the same diseases are also licensed, but are only available with a private prescription or for high-risk pre-term infants in the public health program. We analyzed the cost of switching from the current schedule to the alternative schedule with the hexavalent vaccine in Argentina, assuming similar levels of effectiveness. Methods The study population was infants ≤ 1 year of age born in Argentina from 2015 to 2019. The analysis considered adverse events, programmatic, logistic, and vaccine costs of both schemes from the societal perspective. The societal costs were disaggregated to summarize costs incurred in the public sector and with vaccination pre-term infants in the public sector. Costs were expressed in 2021 US Dollars (US$). Results Although the cost of vaccines with the alternative scheme would be US$39.8 million (M) more than with the current scheme, these additional costs are in large part offset by fewer adverse event-associated costs and lower programmatic costs such that the overall cost of the alternative scheme would only be an additional US$3.6 M from the societal perspective. The additional cost associated with switching to the alternative scheme in the public sector and with the vaccination of pre-term infants in the public sector would be US$2.1 M and US$84,023, respectively. Conclusions The switch to an alternative scheme with the hexavalent vaccine in Argentina would result in marginally higher vaccine costs, which are mostly offset by the lower costs associated with improved logistics, fewer separate vaccines, and a reduction in adverse events.